From the editors: JWR past, present and future. (2nd July 2020) - Pitt, Leyland; Treen, Emily
ABSTRACT: The editor and assistant editor consider the past, present and future of the Journal of Wine Research. They contemplate its origins as a unique journal serving those who grow wine, make wine, sell wine and consume wine. They also observe the current state of the journal, and outline where the journal might go in the future.